2002
DOI: 10.1055/s-2002-35610
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal Agenesis: Report of Three Cases and Review of the Literature

Abstract: Isolated type III tracheal agenesis without associated congenital anomalies is very rare. Therefore, infants with this type of isolated defects are potential candidates for surgical correction. We present three cases of tracheal agenesis (Floyd's type III) with no other major abnormalities and reviewed the literature. We also discussed the previously attempted surgical procedures with the hope that in future, with advances in surgical reconstruction, there may be a better solution for this lethal anomaly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 6 publications
0
13
0
1
Order By: Relevance
“…The incidence of this rare anomaly is reported to be less than 1:50,000 with a male predominance [2]. This condition was first described by Payne in 1900.…”
Section: Discussionmentioning
confidence: 97%
“…The incidence of this rare anomaly is reported to be less than 1:50,000 with a male predominance [2]. This condition was first described by Payne in 1900.…”
Section: Discussionmentioning
confidence: 97%
“…In 1979, Faro et al reported a more detail classification of tracheal agenesis (7 types) based on the literature review [3]. To our best knowledge, 144 cases of tracheal agenesis, including 19 of type I, 87 of type II and 38 of type III, have been reported in the English literature [4][5][6][7][8][9][10][11]. In 1963 Fonkalsrud et al reported a case who survived for 6 weeks after reconstructive surgery including trachealizing the esophagus,dividing the distal esophagus and inserting a gastrostomy tube [12].…”
Section: Discussionmentioning
confidence: 99%
“…Fewer than 100 cases have been reported in the literature until today. The incidence of it was reported to be less than 1:50,000 with a male predominance [1,4]. It presents immediately at birth with cyanosis and respiratory distress.…”
Section: Discussionmentioning
confidence: 99%